2021
DOI: 10.1093/bjc/azab072
|View full text |Cite
|
Sign up to set email alerts
|

Coercive Control: Patterns in Crimes, Arrests and Outcomes for a New Domestic Abuse Offence

Abstract: Critics of the criminalization of coercive control warned that the criminal justice system was ill-prepared for a conceptualization of domestic abuse that relies on victim accounts of fear and manipulation rather than on evidence of violence. Using data obtained through Freedom of Information requests to police forces and aggregated police records, this paper presents police force-level and nationwide patterns in recorded crimes, police arrests and crime outcomes for this new crime and shows that, nationally, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Coercive controlling abuse can be more devastating and salient to victims than physical violence ( Stark, 2012 ) yet coercive control crimes remain far less likely to be prosecuted than domestic abuse crimes in general ( Brennan & Myhill, 2022 ). Using chemical control in the ways illustrated in this paper can mean that perpetrators do not necessarily need to use physical violence to coerce and control the victim, which would be more likely to bring them to the attention of the authorities.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Coercive controlling abuse can be more devastating and salient to victims than physical violence ( Stark, 2012 ) yet coercive control crimes remain far less likely to be prosecuted than domestic abuse crimes in general ( Brennan & Myhill, 2022 ). Using chemical control in the ways illustrated in this paper can mean that perpetrators do not necessarily need to use physical violence to coerce and control the victim, which would be more likely to bring them to the attention of the authorities.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…To date, research suggests criminal justice professionals may still be missing key opportunities for identifying patterned abuse and that the coercive control offence is not being used to its full potential ( Barlow et al, 2020 ; Brennan & Myhill, 2022 ). A qualitative review of 18 cases prosecuted under s.76 found that the law on coercive control was being correctly applied to historical patterns of abuse that included multiple elements of coercion and control; that prosecutors were tapping repetitive physical and sexual abuse to show the “serious effect” required by the law; and that the vast majority of convicted offenders have received significant time in prison, up to a maximum of 6.6 years ( Stark and Hester (2019) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation